(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: Patchy alopecia is a common dermatological problem worldwide with a high degree of phenotypic and genotypic variation influenced by genetic and environmental factors and is often a major source of psychological distress to patients. However, there is limited published data on patchy alopecia in Bangladesh. The purpose of this study was to evaluate the clinical pattern and prevalence of patchy alopecia in Bangladeshi patients. Materials and methods: This is a descriptive cross-sectional study which was carried out in the Department of Dermatology and Venereology of Chittagong Medical College Hospital, Bangladesh, between the periods of September 2018 to December 2019. Results: Out of 259 patients, male were 169 (65.3%) and female were 90 (34.7%) with a male to female ratio 1.8:1. The mean age of the study population was 23.73 ± 12.735 SD (Range: 1-65) years. The mean age of onset was 22.67 ± 12.735SD (Range: 0-65) years. Non Cicatricial Alopecia (NCA) were accounted 192 (74%) and rest of the 67 (26%) were Cicatricial Alopecia (CA) patients. Alopecia Areata (AA) 172 (66.4%) was the most common 192 (74%) NCA while alopecia due to Discoid Lupus Erythematosus (DLE) 34(13.1%) was the most common 67 (26%) CA. Most of the patients 158 (61%) had multiple patches. Among 259 patients, 77 (29.73%) patients had associated pruritus, 44 (16.98%) patients had scaling and 49 (18.9%) patients were atopic. Conclusion: This study finding showed that patchy hair loss results from a variety of causes. Proper identification and differentiation of pattern of patchy alopecia is necessary for early diagnosis and to design appropriate treatment and by all these means to improve the quality of life Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 27-30